Pengembangan Buku Suplemen IPS Pendamping Pembelajaran Kelas IV Berbasis Kearifan Lokal Kota Singkawang SDN 15 Singkawang - Uray Annisa Nurul Melini Anwar; Siti Halidjah; Suparjan Suparjan; Asmayani Salimi; Rio Pranata (ISLAMIKA, 2023)
This study aims to develop social science supplement book products based on local wisdom in Singkawang City for grade IV elementary schools to assist learning activities in the Independent Curriculum. This research and development (RnD) adopted the Borg & Gall model. Data were obtained from 22 fourth-grade students of State Elementary School 15 Singkawang, 1 class teacher, and 3 validators consisting of 1 material, design, and language expert. The data collection method used interviews and questionnaires. The results showed that the development of social science supplement books based on local wisdom in Singkawang City had gone through 7 out of 10 steps. The validity of the developed product obtained very good criteria with an average percentage value of 95% on the material aspect, 95% on the design aspect, and 97.2% on the language aspect. The results of the teacher's response showed very good criteria with an average percentage value of 91.67%. The results of student responses in the first trial showed an average percentage value of 96% with very feasible criteria, and the second trial had an average percentage value of 90.9% with very feasible criteria.